Green infrastructure has weak conceptual links with efficient biodiversity conservation - Johan Ekroos; Maria von Post; Anna S. Persson; Martin Stjernman; Ola Olsson (Ambio, 2025)
To reverse biodiversity loss, creating resilient ecological networks has been promoted in policy and practice. However, we argue that emphasising networks within policy without clear conservation prioritisations may direct focus away from ecological processes important for population persistence. We studied the rationale for resilient ecological networks represented in a policy context, by reviewing research related to biodiversity within the concept of green infrastructure in European policy. We compared this outcome with underlying empirical evidence for effects of landscape properties on ecological processes relevant to population persistence. We show that interventions within green infrastructure research partly diverge from evidence of efficient conservation derived from empirical studies, likely linked to an insufficient acknowledgement of ecological processes determining long-term conservation of populations in GI policy and research. We discuss possible implications for biodiversity conservation and argue for upcoming policies to better integrate scientific evidence and underlying ecological processes to improve biodiversity outcomes.

A new era for science-industry research collaboration – a view towards the future - Matthew R. Baker; Nathalie A. Steins; Martin A. Pastoors; Stefan Neuenfeldt; Andries de Boer; Dirk Haasnoot; Stephanie Madsen; Johan Muller; Kobus Post; Claus R. Sparrevohn; Mart van der Meij (Frontiers in Marine Science, 2023)
Direct engagement of the fishing industry in the provision and co-creation of knowledge and data for research and management is increasingly prevalent. In both the North Atlantic and North Pacific, enhanced and targeted engagement is evident. More is needed. Science-Industry collaborative approaches to developing questions, collecting data, interpreting data, and sharing knowledge create opportunities for information transfer and improved understanding of ecosystem interactions, stock dynamics, economic incentives, and response to management. These collaborations require clear communication and awareness of objectives and outcomes. These initiatives also require careful attention to conditions and interactions that foster respect, trust, and communication. Respect is critical and entails acknowledging the respective skills and expertise of both scientists and fishers. Trust is needed to build confidence in the information developed and its use. Communication is essential to maintain relationships and leverage shared insights. To assess current trends and future opportunities related to this type of engagement, we convened a networking session of research scientists, industry scientists, industry leaders, and fishers at the Annual Science Meeting of the International Council for the Exploration of the Sea (ICES) to address the following questions: (1) What are scientific needs that could be addressed with industry-collected data or knowledge? And (2) How can science-industry collaboration be made sustainable? Here we identify opportunities and acknowledge challenges, outline necessary conditions for respectful and sustainable collaborative research, and highlight ways to promote stakeholder involvement in developing science. We address industry concerns and solicit industry advice. We also address challenges to scientists in ensuring standards for scientific data, conflict of interest, and applying information to advise management. The discussions in this session and subsequent correspondence have led to a set of guidelines and best practices that provide a framework to advance further collaboration between industry and research science. We identify opportunities for directed engagement. We also detail potential approaches to clarify expectations and develop avenues for iterative communication and engagement to sustain collaborative efforts over time. The intent is to improve and expand data streams and contextual understanding of ecosystem processes, stock assessment, and socio-economic dynamics to the benefits of science and industry alike.

Capturing the SARS-CoV-2 infection pyramid within the municipality of Rotterdam using longitudinal sewage surveillance - Miranda de Graaf; Jeroen Langeveld; Johan Post; Christian Carrizosa; Eelco Franz; Ray W. Izquierdo-Lara; Goffe Elsinga; Leo Heijnen; Frederic Been; Janko van Beek; Remy Schilperoort; Rianne Vriend; et al. (Science of The Total Environment, 2023)

Monitoring organic micropollutants in stormwater runoff with the method of fingerprinting - Jeroen G. Langeveld; Johan Post; Konstantinos F. Makris; Bert Palsma; Melanie Kuiper; Erik Liefting (Water Research, 2023)

Rise and fall of SARS-CoV-2 variants in Rotterdam: Comparison of wastewater and clinical surveillance - Ray W. Izquierdo-Lara; Leo Heijnen; Bas B. Oude Munnink; Claudia M.E. Schapendonk; Goffe Elsinga; Jeroen Langeveld; Johan Post; Divyae K. Prasad; Christian Carrizosa; Frederic Been; Janko van Beek; Remy Schilperoort; et al. (Science of The Total Environment, 2023)

Publisher Correction to: Background invertebrate herbivory on dwarf birch (Betula glandulosa-nana complex) increases with temperature and precipitation across the tundra biome - Isabel C. Barrio; Elin Lindén; Mariska Te Beest; Johan Olofsson; Adrian Rocha; Eeva M. Soininen; Juha M. Alatalo; Tommi Andersson; Ashley Asmus; Julia Boike; Kari Anne Bråthen; John P. Bryant; et al. (Polar Biology, 2018)

Background invertebrate herbivory on dwarf birch (Betula glandulosa-nana complex) increases with temperature and precipitation across the tundra biome - Isabel C. Barrio; Elin Lindén; Mariska Te Beest; Johan Olofsson; Adrian Rocha; Eeva M. Soininen; Juha M. Alatalo; Tommi Andersson; Ashley Asmus; Julia Boike; Kari Anne Bråthen; John P. Bryant; et al. (Polar Biology, 2017)

Optimal Flow and Pressure Management in Machine Perfusion Systems for Organ Preservation - Ivo C. J. H. Post; Marcel C. Dirkes; Michal Heger; Rick Bezemer; Johan van ‘t Leven; Thomas M. van Gulik (Annals of Biomedical Engineering, 2012)